Preparation method and application of positive electrode binder
By preparing the modified polyacrylic acid positive electrode binder, a double protective layer is formed, which solves the structural stability, safety hazards and phase fatigue problems of nickel-rich layered positive electrode materials in lithium-ion batteries, and improves the performance and safety of the battery.
Patent Information
- Application Number
- CN202510011411.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-04
AI Technical Summary
Nickel-rich layered cathode material has structural stability problems, safety hazards and phase fatigue in lithium-ion batteries, resulting in a decline in battery performance and an increase in safety risks.
By using the preparation method of a modified polyacrylic acid positive electrode binder, a modified polyacrylic acid binder with a double protective layer is formed by stirring and mixing, heating polymerization, defoaming and cooling of an organic solvent, a monomer component A and a monomer component B. This binder inhibits electrolyte decomposition, transition metal dissolution and phase fatigue in the positive electrode of the lithium battery, and prevents intergranular cracking.
It improves the electrochemical performance and cycle stability of lithium-ion batteries, reduces capacity attenuation, enhances battery safety, and extends the battery life.
Smart Images

Figure CN119751739A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of binders, and in particular to the preparation and application of a modified polyacrylic acid positive electrode binder. Background Art
[0002] Nickel-rich layered cathode materials are a type of cathode material with great development potential in the field of lithium-ion batteries. Their theoretical specific capacity is high, reaching more than 200 mAh g -1 The level of nickel-rich layered cathode materials is higher than that of traditional cathode materials, such as lithium cobalt oxide (LiCoO2), which can store more electricity at the same mass. This makes it possible to improve the energy density of lithium-ion batteries, making the battery have better performance in terms of endurance. For example, in the field of electric vehicles, batteries using nickel-rich layered cathode materials can allow vehicles to travel longer distances. At the same time, as the cobalt content in the cathode material decreases (because the Ni content is relatively high), its cost is also reduced accordingly. For the large-scale application of the lithium-ion battery industry, cost reduction is conducive to its greater competitiveness in the market.
[0003] However, it also faces many challenges, such as: (1) Structural stability issues: high nickel content will make the positive electrode structure unstable during the cycle and accelerate its degradation, especially at the interface with the electrolyte. During the charge and discharge process, due to factors such as changes in the lattice volume and the migration of Ni ions, the crystal structure of the material will be distorted and the layered structure will be destroyed, which will affect the performance and life of the battery. For example, after multiple charge and discharge, the capacity of the battery will decay rapidly and cannot meet the needs of long-term use. (2) Safety hazards: Ni formed during charging 4+ It has high reactivity and can easily cause the dissolution of Ni ions and the decomposition of electrolytes. The gaseous byproducts produced by the decomposition of electrolytes will increase the pressure inside the battery. The oxygen produced during the dissolution of Ni ions is highly oxidizing. These factors combined may cause serious safety problems such as battery bulging, combustion, and even explosion. This is a key issue that needs to be solved in application scenarios with extremely high safety requirements (such as electric vehicles, portable electronic devices, etc.). (3) In polycrystalline nickel-rich positive electrodes, when the H2-H3 phase transition occurs, the lattice volume will change significantly. This change will generate stress, leading to the generation of intergranular cracks. Once intergranular cracks are formed, on the one hand, they will destroy the overall structural integrity of the material, and on the other hand, they will reduce the contact area between the active material and the electrolyte, thereby affecting the transmission of lithium ions and the performance of the battery, resulting in a rapid decline in the battery's charge and discharge performance and failure to achieve the expected use effect.
[0004] As an important component of the electrode, the binder has a significant impact on the interfacial properties of the active material. At present, polyvinylidene fluoride (PVDF) as the mainstream nickel-rich positive electrode binder has many shortcomings. For example, it has the disadvantages of uneven coverage of active material particles and weak van der Waals interactions. As an alternative to polyvinylidene fluoride, biopolymers and synthetic polymers with hydroxyl groups and negatively charged functional groups have been intensively explored. Among them, carboxyl-rich polyacrylic acid (PAA) is an effective binder that promotes excellent adhesion and promotes the formation of an artificial cathode-electrolyte interface layer, thereby improving the electrochemical performance, but the inherent brittleness of polyacrylic acid can easily lead to electrode cracking during cycling. Summary of the invention
[0005] In order to overcome the defects in the prior art, the first purpose of the present invention is to provide a method for preparing a positive electrode binder; the second purpose of the present invention is to provide an application of the positive electrode binder prepared by the method for preparing the positive electrode binder in a lithium battery.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] In a first aspect, the present invention provides a method for preparing a positive electrode binder, comprising the following steps:
[0008] The organic solvent, the A monomer component, and the B monomer component are stirred and mixed uniformly to obtain a mixed solution;
[0009] After heating the mixed solution to a first reaction temperature, adding an initiator and maintaining the first reaction temperature to carry out a reaction;
[0010] A defoamer is added to the mixed solution, and the reaction is carried out by heat preservation after adjusting the temperature from the first reaction temperature to the second reaction temperature. After cooling, a modified polyacrylic acid positive electrode binder is obtained, and the molecular weight of the modified polyacrylic acid positive electrode binder is 10w-100w.
[0011] The invention facilitates the formation of modified polyacrylic acid and makes it have the characteristics of a double protective layer by precisely controlling multiple steps such as selection of monomer components, mixing, polymerization reaction, defoaming and cooling. In the application of lithium battery positive electrode, the characteristics of the double protective layer can inhibit electrolyte decomposition, transition metal dissolution and phase fatigue, prevent intergranular cracking, etc., thereby improving the electrochemical performance and cycle stability of the battery.
[0012] In the stirring and mixing step, the organic solvent, monomer component A, and monomer component B are stirred and mixed uniformly, which is conducive to full contact of the components, making the reaction system uniform, ensuring that the subsequent polymerization reaction can proceed uniformly, and laying the foundation for synthesizing modified polyacrylic acid with uniform structure and performance. If the stirring is uneven, it may cause the local monomer component concentration to be too high or too low, affecting the rate of the polymerization reaction and the consistency of the product, and further affecting the bonding effect of the modified polyacrylic acid positive electrode material and the improvement of battery performance.
[0013] In the polymerization reaction, the mixed solution is heated to the first reaction temperature, and then the initiator is added and the reaction is maintained at this temperature. The appropriate reaction temperature provides the necessary energy for the polymerization reaction, so that the initiator can effectively initiate the polymerization of the monomer components and promote the growth of the molecular chain, thereby forming a modified polyacrylic acid with a certain molecular weight and structure. If the reaction temperature is too low, the polymerization reaction rate is slow, which may lead to problems such as low product molecular weight and insufficient cross-linking degree, affecting its bonding performance as a binder and the effect of improving battery performance; if the reaction temperature is too high, it may trigger side reactions and destroy the product structure, which is also not conducive to its application in lithium batteries.
[0014] During defoaming and cooling, adding a defoaming agent can effectively eliminate bubbles generated during the reaction. Bubbles will affect the structural uniformity of the polymer and reduce its bonding and mechanical properties. After heating to the second reaction temperature, the reaction is kept warm to further promote the polymerization reaction, making the polymer chain more complete and stable, which helps to improve the molecular weight and performance stability of the modified polyacrylic acid.
[0015] The molecular weight of modified polyacrylic acid is controlled within 10w~100w because the suitable molecular weight range enables it to have good bonding properties, flexibility and mechanical strength, and can effectively bond active materials in the positive electrode of lithium batteries, inhibit cracking between grains, and improve the electrochemical performance and cycle stability of batteries. If the molecular weight of modified polyacrylic acid is too small, its bonding performance will be reduced, which is not conducive to the peel strength and cycle performance of the electrode. If the molecular weight of modified polyacrylic acid is too large, the slow dissolution will bring processing difficulties to the lithium battery mixing stage.
[0016] Preferably, the A monomer component is an organic sodium salt. Further preferably, the organic sodium salt is selected from one or more of cyclohexane hexaphosphate sodium salt, sodium methacrylate, and isopropyl cyclopentadiene sodium. Organic sodium salts such as cyclohexane hexaphosphate sodium salt, sodium methacrylate, and isopropyl cyclopentadiene sodium are selected as A monomer components, and these organic sodium salts have specific functional group structures. For example, cyclohexane hexaphosphate sodium salt contains a sodium phosphate group, sodium methacrylate contains a sodium carboxylate group, and isopropyl cyclopentadiene sodium contains a cyclopentadienyl group. These functional groups can interact strongly with the surface of the NCM positive electrode material (ternary positive electrode material, i.e., lithium nickel cobalt manganese oxide), and promote the formation of a thin rock salt phase on the surface of the NCM particles. The rock salt phase has a relatively stable crystal structure, which is tightly attached to the surface of the positive electrode material and becomes a protective structure inside the positive electrode material. During the battery charging and discharging process, the positive electrode material will undergo processes such as changes in the lattice volume. Long-term repeated changes may lead to fatigue of the material structure, i.e., phase fatigue. The existence of the internal thin rock salt phase can buffer the stress caused by this lattice volume change to a certain extent, making the structure of the positive electrode material more stable, reducing the occurrence of phase fatigue, and preventing microcracks between grains.
[0017] Preferably, the B monomer component is acrylic acid. Acrylic acid is the basic monomer component for synthesizing polyacrylic acid. The carboxyl functional group of acrylic acid can react with lithium salts, additives (FEC, TPFPB), oxidized solvents (EC) and other components in the electrolyte, and gradually form a stable interface layer on the surface of the positive electrode material, namely the positive electrode electrolyte interface (CEI layer). The CEI layer covers the surface of the positive electrode material, which can prevent the direct contact between the electrolyte and the positive electrode material, and reduce the possibility of decomposition reaction of the electrolyte under high voltage or other unfavorable conditions. If the electrolyte decomposes, byproducts such as gas will be produced, which will affect the performance of the battery, such as causing an increase in the internal resistance of the battery. For nickel-rich layered positive electrode materials, transition metals such as nickel are easily dissolved into the electrolyte in some cases, which can cause the destruction of the positive electrode material structure and the decline of battery performance. The stable CEI layer can act as a physical barrier to block the diffusion of transition metal ions into the electrolyte, thereby inhibiting the dissolution of transition metals.
[0018] Preferably, the organic solvent is selected from one or more of N-methylpyrrolidone, N-formyl dimethylamine, and acetyl dimethylamine. The above organic solvent has good solubility, and can fully dissolve and evenly disperse the A monomer component and the B monomer component in the reaction system to ensure the smooth progress of the polymerization reaction. A suitable solvent environment helps to control the rate of the polymerization reaction and the molecular weight distribution of the product, so that the modified polyacrylic acid has a uniform structure and performance.
[0019] Preferably, based on 100% by mass, the A monomer component is 25% to 35%, and the B monomer component is 55% to 75%; further preferably, the amount of the organic solvent is 1 to 3 times the total mass of the monomer components. If the A monomer component is too high and the B monomer component is too low, the prepared modified polyacrylic acid positive electrode binder will have insufficient adhesion, low mechanical strength, and insufficient cross-linking network, which will affect the cycle performance of the prepared lithium battery. If the A monomer component is too low and the B monomer component is too high, the chelating effect of the functional part of the A monomer component is not obvious, which is not conducive to the formation of a uniform rock salt phase on the surface. If the organic solvent is excessive, the reaction rate will be reduced.
[0020] Preferably, the first reaction temperature is 30°C to 100°C, and the reaction time at the first reaction temperature is 1h to 7h. The first reaction temperature is 30°C-100°C, and the reaction time is 1h-7h. This temperature range and reaction time enable the initiator to effectively initiate the polymerization of the monomer components, while ensuring that the polymerization reaction proceeds at an appropriate rate. Under this condition, a modified polyacrylic acid with a suitable molecular weight and uniform structure can be formed. If the reaction temperature is too low or the time is too short, the polymerization reaction is incomplete, the product molecular weight is low, and the bonding performance and the improvement effect on battery performance are limited; if the reaction temperature is too high or the time is too long, the product may be excessively cross-linked, the molecular weight distribution may be uneven, or side reactions may occur, affecting the performance stability of the modified polyacrylic acid and the application effect in lithium batteries.
[0021] Preferably, the initiator is selected from one or more of ammonium persulfate, potassium persulfate, and azobisisobutyronitrile. Further preferably, the amount of the initiator is 1 to 5 times the total mass of the monomer component. The initiator can generate free radicals under appropriate reaction conditions to initiate the polymerization reaction of the monomer component. An appropriate amount of initiator can ensure that the polymerization reaction starts smoothly and continues, so that the monomer component is fully converted into a polymer. If the amount of initiator is too little, the polymerization reaction is incomplete and the product performance is poor. If the amount of initiator is too much, it may lead to a too fast reaction rate, generate too much heat, trigger side reactions, affect the structure and properties of the modified polyacrylic acid, and then affect its performance as a positive electrode binder for lithium batteries.
[0022] Preferably, the defoamer is selected from one or more of polyether silicone and gemini glycol polyether. Further preferably, the amount of the defoamer is 0.1 to 4 times the total mass of the monomer component. The above defoamer can effectively reduce the surface tension of the reaction system and eliminate bubbles generated during the reaction. A suitable amount can fully eliminate bubbles without affecting the polymerization reaction, so that the modified polyacrylic acid has a uniform structure. The presence of bubbles will destroy the structural integrity of the polymer, reduce its mechanical properties and bonding properties, and affect the quality of the pole piece and the performance of the battery. By adding an appropriate amount of defoamer, the quality of the modified polyacrylic acid can be improved, thereby improving its application effect in lithium batteries.
[0023] Preferably, the second reaction temperature is 50° C. to 100° C., and the heat preservation reaction time at the second reaction temperature is 1 hour to 7 hours. Through the above reaction, the growth of the polymer chain and the improvement of the structure are promoted, so that the modified polyacrylic acid reaches a suitable molecular weight and performance.
[0024] In a second aspect, the present invention also provides the use of the positive electrode binder prepared by the above-mentioned preparation method of the positive electrode binder in a lithium battery.
[0025] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0026] Modified polyacrylic acid is formed by introducing the organic sodium salt monomer component A into the acrylic acid of the monomer component B. When the modified polyacrylic acid is applied to the positive electrode binder, a double protective layer can be formed. The outer CEI layer can prevent the electrolyte from decomposing and the transition metal from dissolving into the electrolyte. The thin rock salt phase inside can stabilize the structure of the positive electrode material, reduce phase fatigue, and inhibit intergranular cracking. The two work synergistically to protect the positive electrode material from multiple aspects. During high-voltage charging and discharging or long-term use, the double protective layer can maintain the stability of the positive electrode material, reduce capacity attenuation, and effectively improve the performance and cycle life of the lithium-ion battery.
[0027] In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are specifically cited below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 It is a schematic diagram of the modified polyacrylic acid positive electrode binder in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Embodiment 1:
[0032] Step 1: Prepare the mixed solution
[0033] Weigh 30% of the total mass of the monomer components, 70% of the total mass of the monomer components, and 200% of the total mass of the monomer components. In a 2L five-necked round-bottom flask equipped with a nitrogen introduction device, a mechanical stirring device, a reflux condenser, and a thermometer, add the above-mentioned weighed cyclohexane hexaphosphate sodium salt, acrylic acid, and N-vinyl pyrrolidone. After the addition is completed, turn on the stirring device, set the speed to 80r / min, and continue stirring for 150min to ensure that the components are fully mixed and uniform, thereby preparing a mixed solution. The total mass of the monomer components is the mass of the A monomer component (cyclohexane hexaphosphate sodium salt) plus the mass of the B monomer component (acrylic acid).
[0034] Step 2: Polymerization
[0035] After the mixed solution is prepared, nitrogen is passed through and the temperature is raised to 80°C. After the temperature is raised to 80°C, ammonium persulfate accounting for 1% of the total weight of the monomer components is added to the flask. The temperature of the mixed solution is maintained constant at 80°C, the stirring speed is adjusted to 100 r / min, and the stirring reaction is continued for 3 hours.
[0036] Step 3: Defoaming and continuing reaction
[0037] After the polymerization reaction was completed for 3 hours, 0.3% of the total weight of the monomer components of polyether silicone was added to the mixed solution. The reaction temperature was adjusted from 80°C to 60°C and kept warm. The stirring speed was adjusted to 50r / min, and the stirring reaction was continued for 2 hours. After the reaction was completed, the heating, stirring and nitrogen introduction were stopped, and the mixed solution was allowed to cool naturally to obtain a modified polyacrylic acid positive electrode binder, see Figure 1 shown.
[0038] Embodiment 2:
[0039] Step 1: Prepare the mixed solution
[0040] Weigh 30% of the total mass of the monomer components, 70% of the total mass of the monomer components, and 300% of the total mass of the monomer components. In a 2L five-mouth round-bottom flask equipped with a nitrogen introduction device, a mechanical stirring device, a reflux condenser and a thermometer, add the above-mentioned weighed propyl cyclopentadiene sodium, acrylic acid and N-vinyl pyrrolidone. After the addition is complete, turn on the stirring device, set the speed to 80r / min, and continue stirring for 20min to ensure that each component is fully mixed, thereby preparing a mixed solution. The total mass of the monomer components is the mass of the A monomer component (propyl cyclopentadiene sodium) plus the mass of the B monomer component (acrylic acid).
[0041] Step 2: Polymerization
[0042] After the mixed solution is prepared, nitrogen is passed through and the temperature is raised to 70° C. After the temperature is raised to 80° C., 1% of azobisisobutyronitrile by weight of the total monomer component is added to the flask. The temperature of the mixed solution is maintained constant at 70° C., the stirring speed is adjusted to 100 r / min, and the stirring reaction is continued for 3 hours.
[0043] Step 3: Defoaming and continuing reaction
[0044] After completing the polymerization reaction for 3 hours, add 0.5% of the total weight of the monomer components into the mixed solution. Adjust the reaction temperature from 70°C to 60°C and keep warm. Adjust the stirring speed to 50r / min, and continue stirring the reaction for 1.5 hours. After the reaction is completed, stop heating, stirring and nitrogen gas, and allow the mixed solution to cool naturally to obtain a modified polyacrylic acid positive electrode binder.
[0045] Embodiment 3:
[0046] The modified polyacrylic acid positive electrode binder prepared in Examples 1 and 2 of the present invention and the commercially available polyvinylidene fluoride (PVDF) positive electrode binder were subjected to a buckling performance test experiment.
[0047] Preparation of positive electrode slurry of nickel cobalt manganese oxide (NCM) for lithium-ion batteries:
[0048] 18 g of the modified polyacrylic acid positive electrode binder prepared in Example 1 and Example 2 and two commercially available polyvinylidene fluoride (PVDF) positive electrode binders from different manufacturers were weighed respectively. One commercially available polyvinylidene fluoride was Solvay PVDF5130, which was used as Comparative Example 1. The other commercially available polyvinylidene fluoride was Arkema HSV900, which was used as Comparative Example 2.
[0049] The above four positive electrode binders were respectively dissolved in 400 g of N-methylpyrrolidone solvent to prepare four mixed solutions.
[0050] To each mixed solution, 564 g NCM and 18 g carbon black were added in turn, the speed was set to 120 r / min, and the mixture was stirred for 30 min to allow the powder materials to be fully and evenly mixed in the solvent to obtain NCM positive electrode slurry.
[0051] Production of button lithium-ion battery:
[0052] The prepared positive electrode slurry was evenly coated on the surface of the aluminum foil, and then the aluminum foil coated with the slurry was placed in a vacuum environment and dried at a temperature of 110°C overnight to prepare the positive electrode.
[0053] 95% graphite, 1.5% conductive carbon, 1.5% sodium carboxymethyl cellulose and 2% styrene butadiene rubber were mixed in corresponding proportions and coated on copper foil, which was also placed in a vacuum environment and dried at 60°C overnight to prepare a negative electrode.
[0054] 1 mol of lithium hexafluorophosphate (LiPF6) was selected as the lithium salt, and the solvent was a mixed solvent composed of ethylene carbonate (EC), diethyl carbonate (DC), and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1 as the electrolyte. A porous glass fiber was used as the separator to assemble a button-type lithium-ion battery.
[0055] Use constant current charge and discharge mode to charge and discharge at room temperature and high temperature, the voltage range is 2.8 ~ 4.7V, first 0.1C cycle 3 times, then 0.3C charge and discharge cycle 300 times (1C = 230mAg -1 ). The experimental results are shown in Table 1 below.
[0056]
[0057] It can be seen from the experimental results that the modified PAA positive electrode binder prepared by Examples 1 and 2 of the present invention has a high first efficiency, excellent cycle performance with a charge cutoff of up to 4.7V, and a high capacity retention rate compared to the two commercially available PVDFs of Comparative Examples 1 and 2.
[0058] Embodiment 4:
[0059] The modified polyacrylic acid positive electrode binder prepared in Examples 1 and 2 of the present invention and the commercially available polyvinylidene fluoride (PVDF) positive electrode binder were tested for the flexibility of the electrode piece.
[0060] Preparation of positive electrode slurry of nickel cobalt manganese oxide (NCM) for lithium-ion batteries:
[0061] 18 g of the modified polyacrylic acid positive electrode binder prepared in Example 1 and Example 2 and two commercially available polyvinylidene fluoride (PVDF) positive electrode binders from different manufacturers were weighed respectively. One commercially available polyvinylidene fluoride was Solvay PVDF5130, which was used as Comparative Example 3. The other commercially available polyvinylidene fluoride was Arkema HSV900, which was used as Comparative Example 4.
[0062] The above four positive electrode binders were respectively dissolved in 400 g of N-methylpyrrolidone solvent to prepare four mixed solutions.
[0063] To each mixed solution, 564 g NCM and 18 g carbon black were added in turn, the speed was set to 120 r / min, and the mixture was stirred for 30 min to allow the powder materials to be fully and evenly mixed in the solvent to obtain NCM positive electrode slurry.
[0064] Pole flexibility test:
[0065] The prepared positive electrode slurry was evenly coated on the surface of the aluminum foil, and then the aluminum foil coated with the slurry was placed in a vacuum environment and dried overnight at a temperature of 110°C to prepare the positive electrode. The number of turns and cracks were observed using 3mm, 5mm, and 7mm winding needles. The experimental results are shown in Table 2 below.
[0066]
[0067] It can be seen from the experimental results that the positive electrode prepared by the positive electrode binder prepared in Example 1 and Example 2 of the present invention has a more obvious effect on improving the flexibility of the electrode sheet than the positive electrode prepared by the positive electrode binder of Comparative Example 3 and Comparative Example 4.
[0068] The present invention uses specific embodiments to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A method for preparing a positive electrode binder, characterized in that: The steps include: The organic solvent, the A monomer component, and the B monomer component are stirred and mixed uniformly to obtain a mixed solution; After heating the mixed solution to a first reaction temperature, adding an initiator and maintaining the first reaction temperature to carry out a reaction; A defoamer is added to the mixed solution, and the reaction is carried out by heat preservation after adjusting the temperature from the first reaction temperature to the second reaction temperature. After cooling, a modified polyacrylic acid positive electrode binder is obtained, and the molecular weight of the modified polyacrylic acid positive electrode binder is 10w-100w.
2. The method for preparing a positive electrode binder according to claim 1, characterized in that: The A monomer component is an organic sodium salt; Preferably, the organic sodium salt is selected from one or more of cyclohexanehexol hexaphosphate sodium salt, sodium methacrylate, and sodium isopropylcyclopentadiene.
3. The method for preparing a positive electrode binder according to claim 1, characterized in that: The B monomer component is acrylic acid.
4. The method for preparing a positive electrode binder according to claim 1, characterized in that: The organic solvent is selected from one or more of N-methylpyrrolidone, N-formyl dimethylamine and acetyl dimethylamine.
5. The method for preparing a positive electrode binder according to claim 1, characterized in that: Based on 100% by mass, the A monomer component is 25% to 35%, and the B monomer component is 55% to 75%; Preferably, the amount of the organic solvent used is 1 to 3 times the total mass of the monomer components.
6. The method for preparing a positive electrode binder according to claim 1, characterized in that: The first reaction temperature is 30° C. to 100° C., and the reaction time at the first reaction temperature is 1 h to 7 h.
7. The method for preparing a positive electrode binder according to claim 1, characterized in that: The initiator is selected from one or more of ammonium persulfate, potassium persulfate, and azobisisobutyronitrile; Preferably, the amount of the initiator used is 1 to 5 times the total mass of the monomer components.
8. The method for preparing a positive electrode binder according to claim 1, characterized in that: The defoamer is selected from one or more of polyether silicone and gemini acetylene glycol polyether; Preferably, the amount of the defoaming agent used is 0.1 to 4 times the total mass of the monomer components.
9. The method for preparing a positive electrode binder according to claim 1, characterized in that: The second reaction temperature is 50° C. to 100° C., and the insulation reaction time at the second reaction temperature is 1 h to 7 h.
10. Use of the positive electrode binder prepared by the method for preparing the positive electrode binder according to any one of claims 1 to 9 in lithium batteries.
Citation Information
Cited By
Preparation method and application of lithium ion battery positive electrode slurry based on fluoride-free binder
CN120657131A